2023
DOI: 10.3390/su15054312
|View full text |Cite
|
Sign up to set email alerts
|

Participatory Evaluation of Sorghum Processing and Sensory Attributes in Mali: Methodology for Improving Food Security Outcomes from Variety Development Efforts

Abstract: A requirement for the successful development of new sorghum varieties in Mali is effective evaluation of grain qualities, since sorghum is a staple food crop on which farmers rely for food security. The diversity of grain quality and social aspects that determine varietal acceptability for processing and cooking, however, make this a challenging task. As the processors of sorghum grain in households, women’s knowledge of grain quality traits can contribute to this work. Our objective is to understand opportuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Furthermore, a recent review of gender and plant breeding research showed that even when genderdifferentiated data were collected for assessing farmers' preferences for plant traits, gender differentiated analyses were rare (Weltzien et al, 2019a). Recent efforts have focused on interdisciplinary research that examines how roles and responsibilities in crop and seed production, processing, cooking, and marketing influences these trait preferences (Diallo et al, 2018;Marimo et al, 2020;Isaacs et al, 2023). Teeken et al (2021) examined how intersectional identities shaped cassava trait preferences, finding that food product quality traits were more important to food insecure households, and women and men's preferences varied by region, wealth, and household characteristics.…”
Section: Gender In Plant Breedingmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, a recent review of gender and plant breeding research showed that even when genderdifferentiated data were collected for assessing farmers' preferences for plant traits, gender differentiated analyses were rare (Weltzien et al, 2019a). Recent efforts have focused on interdisciplinary research that examines how roles and responsibilities in crop and seed production, processing, cooking, and marketing influences these trait preferences (Diallo et al, 2018;Marimo et al, 2020;Isaacs et al, 2023). Teeken et al (2021) examined how intersectional identities shaped cassava trait preferences, finding that food product quality traits were more important to food insecure households, and women and men's preferences varied by region, wealth, and household characteristics.…”
Section: Gender In Plant Breedingmentioning
confidence: 99%
“…Sorghum production contributed to their food and nutrition security. interdisciplinary team of nutritionists, breeders, and social scientists developed this culinary test methodology in which the women evaluate the grain quality attributes, decorticate the grain, cook the sorghum into a commonly eaten food, tô, and men and women evaluate the sensory qualities of the tô (taste, color, texture, conservation) (Isaacs et al, 2023). After several years, this method was validated in 2006 across different zones and compared with laboratory tests.…”
mentioning
confidence: 99%
See 3 more Smart Citations